Healthcare 4.0 : health informatics and precision data management - Krishnasamy, Lalitha; Dhanaraj, Rajesh Kumar; Balusamy, Balamurugan; Sabharwal, Munish; Chinnasamy, Poongodi (Boca Raton : Chapman & Hall/CRC, 2022)
The main aim of Healthcare 4.0: Health Informatics and Precision Data Management is to improve the services given by the healthcare industry and to bring meaningful patient outcomes by applying the data, information and knowledge in the healthcare domain. Features: Improves the quality of health data of a patient Presents a wide range of opportunities and renewed possibilities for healthcare systems Gives a way for carefully and meticulously tracking the provenance of medical records Accelerates the process of disease-oriented data and medical data arbitration Brings meaningful patient health outcomes Eradicates delayed clinical communications Helps the research intellectuals to step down further toward the disease and clinical data storage Creates more patient-centered services The precise focus of this handbook is on the potential applications and use of data informatics in healthcare, including clinical trials, tailored ailment data, patient and ailment record characterization and health records management.
OCLC-licensed vendor bibliographic record.
Keywords: Medical informatics; Health services administration -- Technological innovations; COMPUTERS / Database Management / Data Mining; COMPUTERS / Information Technology; HEALTH & FITNESS / General